USABILITY TESTING OF VIRTUAL KEYBOARD IN TOUCH SCREEN WITH QUESTIONNAIRE METHOD - Pangetsu, Harijanto (CommIT (Communication and Information Technology) Journal, 2014)
A system consists of input, process, and output. User interface is a place for users to interact in the system where one of the functions is as input facility of the system. One of the input tools is keyboard. With the development of touchscreen, then virtual keyboard is required. A good interface must be able to be used easily especially for novice users. The usability testing is required to know the usability level of the interface. A good usability has characteristics of effective to use (effectiveness), efficient to use (efficiency), safe to use (safety), having good utility (utility), easy to learn (learnability) and easy to remember how to use (memorability). Usability testing is an evaluation approach involving users. With usability testing, it is expected that it can give positive inputs in designing an interface especially virtual keyboard interface mainly with the characteristics of easy to learn (learnability), and easy to remember how to use (memorability) so that the resulted design can have good usability level